Current Insights of the Potential Plant Bioactive Compounds on Modulating the mTOR Signaling Pathway in Regulating Oncological Disorders - Khanal, Sonali; Pillai, Manjusha; Bhuia, Md Shimul; Islam, Muhammad Torequl; Sharma, Onkar; Verma, Rachna; Nepovimova, Eugenie; Kuca, Kamil; Kumar, Dinesh; Chowdhury, Raihan (Phytotherapy research, 2025)
Deregulation of the mechanistic target of the rapamycin (mTOR) pathway plays an important role in cancer genesis and progression, making it an attractive target for cancer treatment. Disrupting the mTOR pathway contributes to uncontrolled cell growth, increased proliferation, and enhanced cell survival, all of which are hallmarks of cancer. The findings imply that the deregulation of the mTOR pathway in cancer provides a compelling basis for therapeutic treatments. Phytochemicals such as flavonoids and polyphenols have been shown to play a key role in suppressing different kinases implicated in PI3K/AKT/mTOR signaling cascades. A thorough study of the molecular connections between bioactive substances, mTOR signaling, and autophagy activation can lead to the creation of personalized treatments that work better and have fewer side effects. Finding out how important it is to target the mTOR pathway and how to use bioactive chemicals from plants to treat cancer are both important discoveries that could lead to more precise medicine and the development of effective cancer drugs. Finally, targeting mTOR pathways using plant-derived chemicals may be a promising therapy strategy for cancer. This review tries to summarize putative plant bioactive chemicals that act on malignancies via mTOR signaling pathways. Furthermore, the paper discusses the role of the mTOR pathway in cancer, specifically its influence on cell growth, proliferation, and survival.
Keywords: pharmacology; autofagie; Phytochemicals; fytonutrienty; Antineoplastic Agents, Phytogenic; Neoplasms; Cell Proliferation; oncology; plant bioactive compounds; signální transdukce; TOR serin-threoninkinasy; Signal Transduction; TOR Serine-Threonine Kinases; autophagy; Animals; Autophagy; lidé; Humans; zvířata; proliferace buněk; apoptosis; nádory; fytogenní protinádorové látky; mTOR signaling pathway